Augmentation of Extracellular ATP Synergizes With Chemotherapy in Triple Negative Breast Cancer - Manouchehri, Jasmine M.; Datta, Jharna; Willingham, Natalie; Wesolowski, Robert; Stover, Daniel; Ganju, Ramesh K.; Carson, William E.; Ramaswamy, Bhuvaneswari; Cherian, Mathew A. (Frontiers in Oncology, 2022)
Introduction: Breast cancer affects two million women worldwide every year and is the most common cause of cancer-related death among women. The triple-negative breast cancer (TNBC) sub-type is associated with an especially poor prognosis because currently available therapies, fail to induce long-lasting responses. Therefore, there is an urgent need to develop novel therapies that result in durable responses. One universal characteristic of the tumor microenvironment is a markedly elevated concentration of extracellular adenosine triphosphate (eATP). Chemotherapy exposure results in further increases in eATP through its release into the extracellular space of cancer cells via P2RX channels. eATP is degraded by eATPases. Given that eATP is toxic to cancer cells, we hypothesized that augmenting the release of eATP through P2RX channels and inhibiting extracellular ATPases would sensitize TNBC cells to chemotherapy. Methods: TNBC cell lines MDA-MB 231, Hs 578t and MDA-MB 468 and non-tumorigenic immortalized mammary epithelial MCF-10A cells were treated with increasing concentrations the chemotherapeutic agent paclitaxel in the presence of eATPases or specific antagonists of P2RXs with cell viability and eATP content being measured. Additionally, the mRNA, protein and cell surface expressions of the purinergic receptors P2RX4 and P2RX7 were evaluated in all examined cell lines via qRT-PCR, western blot, and flow cytometry analyses, respectively. Results: In the present study, we observed dose-dependent declines in cell viability and increases in eATP in paclitaxel-treated TNBC cell lines in the presence of inhibitors of eATPases. These effects were reversed by specific antagonists of P2RXs. Similar results were observed with P2RX activators. All examined cell lines expressed both P2RX4 and P2RX7 at the mRNA, protein and cell surface levels. Conclusion: These results reveal that eATP modulates the chemotherapeutic response in TNBC cell lines which could be exploited to enhance the efficacy of chemotherapy regimens for TNBC.